Chemoreceptor discharges and cytochrome redox changes of the rat carotid body: Role of heme ligands - Lahiri, Sukhamay (The National Academy of Sciences, 1999)
In superfused in vitro rat carotid body, we recorded chemoreceptor discharges and the redox state of cytochromes simultaneously to identify the primary oxygen-sensing protein controlling transmitter release and electrical activity of the carotid sinus nerve. These parameters were tested under the influence of heme ligands such as oxygen, cyanide, 4-(2-aminoethyl)-benzenesulfonyl fluoride, and CO. During stimulation, there was an initial increase in discharge frequency followed by a decline or suppression of activity. Photometric changes lagged and were maintained as nerve activity decreased. Reducing mitochondrial cytochromes by cyanide or prolonged severe hypoxia, suppressed the chemoreceptor discharge. 4-(2-Aminoethyl)-benzenesulfonyl fluoride, a specific inhibitor of the phagocytic cytochrome b(558), also silenced the chemoreceptors after an initial excitation. CO increased the chemoreceptor discharge under normoxia, an effect inhibited by light, when the cytochromes were not reduced. When the discharges were depressed by severe hypoxia, exposure to light excited the chemoreceptors and the cytochromes were reduced. The rapidity of the chemosensory responses to light and lack of effect on dopamine release from type I cells led us to hypothesize that carotid body type I cells and the apposed nerve endings use different mechanisms for oxygen sensing: the nerve endings generate action potentials in association with membrane heme proteins whereas cytosolic heme proteins signal the redox state, releasing modulators or transmitters from type I cells.